A priceless gift – Reflections on Richard Slaughter's influence on working and living with the future. (September 2021) - Morrow, Rowena
Highlights: During the 2000's, Richard Slaughter taught and influenced a generation of foresight practitioners. Futures Studies involves consciously developing new ways of thinking about how futures might emerge, change and shift. Richard's work supported us to identify the possibilities that might lie on the other side of a civilizational understanding of planetary limits. We were asked to consciously develop ways of thinking, to create new neural pathways, in order to start to understand how to consider multiple futures. Abstract: Richard Slaughter's approach to understanding and teaching futures studies is foundational to the thinking and practice of the more than 160 students that went through the Master of Strategic Foresight program at Swinburne University of Technology in Melbourne, Australia. I studied with Richard, worked with him and have been guided by his approach in my foresight practice for over 15 years. Richard's contribution to the futures field is exemplified by his understanding of the role the interior development of the foresight practitioner plays in creating images of the future, his articulation of the civilizational challenges we face and his weaving of integral theory and futures thinking. This piece is a reflection on the impact Richard's ideas about possible futures and the practice of foresight has had on the work I, and many others, deliver across numerous contexts and industries.